THE EFFECT OF PROBLEM BASED LEARNING MODEL ON STUDENTS METACOGNITIVE KNOWLEDGE ON ACID BASE MATERIAL - Amruddin, Muh. Fatih; Jusniar, Jusniar; Sugiarti, Sugiarti (UNESA Journal of Chemical Education, 2023)
The aim of this research is to know the influence of learning model problem solving on metacognitive knowledge in class XI IPA at one of state senior high school 10 Makassar on acid base material. Research methods that have been used are quasi-experimental with a quantitative approach and using post-test control group design. The research population is the entire XI IPA class with a total of two classes. Research samples are class XI IPA 6 as an experimental group and class XIIPA 5 as a control group. Data gathering techniques use expression tests to obtain metacognitive knowledge data. Data analysis is done using descriptive and inferential statistics. The results of the statistical analysis obtained the average metacognitive knowledge test of the experimental group 71.2 higher than the control group 58.2. The results of inferential statistical analysis of the metacognitive knowledge test results of the students showed that the data of the experimental and control groups came from homogeneous but not normally distributed populations, so the hypothetical test used was the Mann-Whitney test. From the data the results of the analysis show Zhitung (4.51) > Ztable. (1.64). Based on the results of the analysis, it can be concluded that there is an influence of the learning model Problem Solving on the metacognitive knowledge of students of grade XI High School State 10 Makassar on the acid base material.